Protection and antibody response induced by intramuscular DNA vaccine encoding for viral haemorrhagic septicaemia virus (VHSV) G glycoprotein in turbot (Scophthalmus maximus) - Pereiro, P.; Martinez-Lopez, A.; Falco, A.; Dios, S.; Figueras, A.; Coll, J. M.; Novoa, B.; Estepa, A. (Fish & Shellfish Immunology, 2012)
Turbot (Scophthalmus maximus) is a high-value farmed marine flatfish with growing demand and production levels in Europe susceptible to turbot-specific viral haemorrhagic septicaemia virus (VHSV) strains. To evaluate the possibility of controlling the outbreaks of this infectious disease by means of DNA vaccination, the gpG of a VHSV isolated from farmed turbot (VHSV 860) was cloned into an expression plasmid containing the human cytomegalovirus (CMV) promoter (pMCV1.4-G 860). In our experimental conditions, DNA immunised turbots were more than 85% protected against VHSV 860 lethal challenge and showed both VHSV-gpG specific and neutralizing antibodies. To our knowledge this is the first report showing the efficacy of turbot genetic immunisation against a VHSV. Work is in progress to determine the contribution of innate and adaptive immunity to the protective response elicited by the immunization. © 2012.